FENOMENA ALIH KODE DAN CAMPUR KODE DALAM VIDEO PODCAST DEDDY CORBUIZER DAN AGNEZ MONICA: KAJIAN SOSIOLINGUISTIK - Nisa, Nurul; Nuryeti, Rita; Santoso, Damar Aji; Putri, Friska Ciptasari; Muasomah; Mukhlis, Abdul (JBI : Jurnal Bahasa Indonesia, 2025)
This study aims to examine the phenomenon of code-switching and code-mixing in digital interactions through the analysis of Deddy Corbuzier's podcast episode with Agnez Monica entitled “VIDI: OM balding, AGNEZ MO LOE CELINGKUH1N⁉️DAH G11L444 YA LOE OM " which was uploaded on March 1, 2025 with a duration of 1 hour 35 minutes 41 seconds. The method used is descriptive qualitative with micro sociolinguistic approach through transcription and thematic analysis based on typology Chaer (situational, metaphorical, and identity tagging). The results found 16 code switching and 21 code mixing, with a predominance of external code switching (Indonesian–English) of 68%. Three main communication strategies were identified, namely: (1) situational switching to adjust the topic of conversation, (2) metaphorical switching as a means of humor and emotional suppression, and (3) identity marking through English vocabulary to strengthen the image of Agnez Monica as a global artist. Further analysis showed that 74% of code switching was done by Agnez Monica to affirm professional identity while bridging audiences across generations. These findings confirm that multilingual practice in podcasts serves not only   as a communication strategy, but also as a means of forming cultural identity in the digital space. This study contributes to the development of media sociolinguistic studies by adapting the Chaer model in the context of new media and offering recommendations on communication strategies for content creators in Indonesia.